Clinical and Epidemiological Characteristics of COVID-19 Patients in Chongqing China - Ao Yang; Qian Qiu; Xianghua Kong; Yanyu Sun; Tingying Chen; Yujie Zuo; Danfeng Yuan; Wei Dai; Jihong Zhou; Anzhou Peng (Frontiers in Public Health, 2020)
Objectives: To study in-depth the clinical and epidemiological characteristics of pneumonia resulting from COVID-19 and provide evidence for effective public health decisions.Methods: This was a retrospective, single-center research study. Participants were enrolled from patients presenting at the Chongqing Public Health Medical Treatment Center from Jan 24 to Feb 7, 2020, and were confirmed as having COVID-19.Results: A total of 114 COVID-19 patients (99 mild, 4 severe, 11 critical) of which 56 (56/114; 49.1%) were male, 58 (58/114; 50.9%) were female with a mean age of 46.05 years. Twenty nine (29/114; 25.44%) patients suffered from chronic diseases. Neutrophils counts in 23.68% (27/114) of patients were abnormally low and abnormally high in 21.05% (24/114). Erythrocyte sedimentation rate and the C-reactive protein levels were abnormally elevated in 76.5% (62/81) and 62.9% (66/105) of patients, respectively. Creatine kinase isoenzymes (CK-MB), pro-brain natriuretic peptide (pro-BNP) and troponin levels were above the normal range in 7.10% (8/112), 66.7% (10/15), and 100% of patients, respectively. The percentage of patients in which the partial pressure of oxygen (PaO2)/fraction of inspired O2(FiO2) ratio exceeded 200 was 60%. A total of 91 (91/114; 79.82%) patients displayed severe bilateral pneumonia, 52 (52/114; 45.61%) exhibited ground-glass opacity, and pulmonary consolidation was observed in 4 (3.51%) patients. Differences in shortness of breath, insomnia, inappetence, the procalcitonin (PCT) levels, FiO2 and PaO2/FiO2 among the three groups were statistically significant (p < 0.05). Differences between the mild and severe groups was observed in neutrophil and lymphocyte counts, CD4 expression, and levels of C-reactive protein, alanine aminotransferase, aspartate aminotransferase and albumin (P < 0.05). Between the mild and critical groups, differences were observed in neutrophils, platelets, and CD4 expression (P < 0.05). A difference in C-reactive protein levels between severe and critical groups was also found (P < 0.05).Conclusions: In the majority of cases no gender differences were observed and mostly the symptoms were mild. Evidence of efficient human-to-human virus transmission was found. The elderly with comorbidities were more prone to develop into severe or critical illness. Age and comorbidity may be risk factors for poor outcome.